2020
DOI: 10.1001/jama.2020.14185
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intra-arrest Transport vs Continued On-Scene Resuscitation With Survival to Hospital Discharge Among Patients With Out-of-Hospital Cardiac Arrest

Abstract: IMPORTANCE There is wide variability among emergency medical systems (EMS) with respect to transport to hospital during out-of-hospital cardiac arrest (OHCA) resuscitative efforts. The benefit of intra-arrest transport during resuscitation compared with continued on-scene resuscitation is unclear.OBJECTIVE To determine whether intra-arrest transport compared with continued on-scene resuscitation is associated with survival to hospital discharge among patients experiencing OHCA. DESIGN, SETTING, AND PARTICIPAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
103
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(116 citation statements)
references
References 37 publications
2
103
2
1
Order By: Relevance
“…28 Another study found that intra-arrest transport was found to be associated with a lower probability of survival and a worse neurologic outcome. 29 Several studies have considered the balance of on-site ALS and transport, finding that 90% of survivors achieved ROSC within 16 min 26 to 24 min, 27 and Kim et al concluded that 21 min was the best time to initiate transport to the hospital. 30 It may not be possible within a group of patients to predict who might benefit from prolonged onscene ALS or transport with ongoing ALS.…”
Section: Discussionmentioning
confidence: 99%
“…28 Another study found that intra-arrest transport was found to be associated with a lower probability of survival and a worse neurologic outcome. 29 Several studies have considered the balance of on-site ALS and transport, finding that 90% of survivors achieved ROSC within 16 min 26 to 24 min, 27 and Kim et al concluded that 21 min was the best time to initiate transport to the hospital. 30 It may not be possible within a group of patients to predict who might benefit from prolonged onscene ALS or transport with ongoing ALS.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to transport a patient in cardiac arrest for ECPR must not compromise the quality of CCPR. 24 Appropriate ECPR-selection criteria and the optimal timing of transfer may be identified from wellconducted randomised trials, including currently recruiting trials, 25 but given the substantial resource cost of ECPR, cost-benefit must also be established. The modelling described here allows for meaningful needs assessment and planning to provide assurance prior to commencement of ECPR programmes.…”
Section: Discussionmentioning
confidence: 99%
“…A critical consideration of any aspiring ECPR programme is to achieve at least equivalent outcomes with those currently attained by conventional measures. The decision to transport a patient in cardiac arrest for ECPR must not compromise the quality of CCPR 24 . Appropriate ECPR‐selection criteria and the optimal timing of transfer may be identified from well‐conducted randomised trials, including currently recruiting trials, 25 but given the substantial resource cost of ECPR, cost–benefit must also be established.…”
Section: Discussionmentioning
confidence: 99%
“…A few observational studies have been conducted to evaluate the effect of the duration of on-scene CPR; however, no large scale randomized study has been conducted on that topic yet. 19,20 The duration of on-site CPR should be determined considering a variety of factors, including the training level of the emergency medical team providing resuscitation (BLS or ALS level), elapsed time from cardiac arrest, and transport time to the hospital. The 2020 guidelines recommend considering transporting the patient to the hospital if restoration of spontaneous circulation is not achieved after 6 minutes of on-site CPR if the resuscitation team can only perform BLS or after 10 minutes of on-site CPR if resuscitation team can perform ALS.…”
Section: Duration Of On-site Cprmentioning
confidence: 99%